Possibilites of isotopes production of ¹⁵³Sm, ¹⁷⁵Yb, ¹⁸⁶Re at the electronic accelerator - Dikiy, N.P.; Krasnoselskiy, N.V.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V.; Uvarov, V.L. (Problems of Atomic Science and Technology, 2023)
Photonuclear technology for producing osteotropic isotopes ¹⁵³Sm (Т₁/₂ = 1.9 days, Eᵦ = 0.8 MeV, Eᵧ = 103.2 keV), ¹⁷⁵Yb (Т₁/₂ = 4.2 days, Eᵦ = 0.5 MeV, Eᵧ = 396.3 keV) and ¹⁸⁶Re (T₁/₂ = 3.8 days, Eᵦ = 1.1 MeV, Eᵧ = 137.2 keV) with using nanoparticles (50…80 nm) of oxides of these elements and the Szilard-Chalmers reac-tion to increase specific activity have been developed at the NSC KIPT electron accelerator. Such medical isotopes are not produced in Ukraine. The overall electron accelerator isotope yield when bremsstrahlung irradiated these samples with a maximum energy of 40 MeV and a current of 250 μA for ¹⁸⁶Re and 13.5 MeV and a current of 500 μA for ¹⁵³Sm and ¹⁷⁵Yb has been shown to have the advantages of higher specific activity, negligible the content of impurities and does not require immobilization of radioactive waste in comparison with a reactor and a cyclotron. На електронному прискорювачі ННЦ ХФТІ розроблені фотоядерні технології одержання остеотропних ізотопів ¹⁵³Sm (Т₁/₂ = 1,9 доби, Eᵦ = 0,8 МеВ, Eᵧ = 103,2 кеВ), ¹⁷⁵Yb (Т₁/₂ = 4,2 доби, Eᵦ = 0,5 МеВ, Eᵧ = 396,3 кеВ) and ¹⁸⁶Re (T₁/₂ = 3,8 доби, Eᵦ = 1,1 МeВ, Eᵧ = 137,2 кеВ) з використанням наночастинок (50…80 нм) оксидів цих елементів та реакції Сциларда-Чалмерса для підвищення питомої активності. В Україні такі медичні ізотопи не виробляються. Показано, що загальний вихід ізотопів на прискорювачі електронів при опроміненні цих зразків гальмівним випромінюванням з максимальною енергією 40 МеВ і струмом 250 μА для ¹⁸⁶Re та 13,5 МеВ і струмом 500 μА для ¹⁵³Sm та ¹⁷⁵Yb має такі переваги, як більш високу питому активність, незначний вміст домішок і не потребує іммобілізації радіоактивних відходів у порівнянні з реактором та циклотроном.